Resistive Switching Characteristics in TiO2/LaAlO3 Heterostructures Sandwiched in Pt Electrodes - Yuyuan Cao; Qitao Di; Lin Zhu; Aidong Li; Di Wu (Advances in Materials Science and Engineering, 2015)
TiO2/LaAlO3 (TiO2/LAO) heterostructures have been deposited on Pt/TiO2/SiO2/Si substrates by pulsed laser deposition. Resistive switching characteristics of Pt/TiO2/LAO/Pt have been studied and discussed in comparison with those of Pt/TiO2/Pt. It is observed that the switching uniformity and the ON/OFF resistance ratio can be greatly improved by introducing the LAO layer. The observed resistive switching characteristics are discussed as a function of LAO thickness and explained by the preferential formation and rupture of conductive filaments, composed of oxygen vacancies, in the LAO layer.